IMPLEMENTASI METODE TILAWATI DALAM MENINGKATKAN BACAAN AL-QUR’AN DI MADRASAH DINIYAH AL-FATTAH DESA TAMBANG, PUDAK, PONOROGO - Ajhuri, Kayyis Fithri; Khoiril Hafidhoh (Kodifikasia, 2024)
This study aims to evaluate the implementation of the Tilawati method in improving Quranic reading skills at Madrasah Diniyah Al-Fattah, Ponorogo. The method is considered effective in accelerating learning processes and enhancing tajweed mastery and accuracy in makhraj pronunciation. Data were collected through observation, interviews, and documentation, with both students and teachers as respondents. The results show significant improvements after applying the Tilawati method. The basic material completion time decreased from 6 months to 3 months. The percentage of students reading fluently increased from 60% to 85%, while tajweed mastery and makhraj accuracy improved from 55% and 50% to 90% and 88%, respectively. Student attendance also increased from 75% to 90%. This study concludes that the Tilawati method is highly effective in enhancing Quranic reading skills in Madrasah Diniyah. Further research is recommended to compare this method with other learning methods and explore the supporting and inhibiting factors in its application.